Untraceable privacy-preserving authentication protocol for RFID tag using salted hash algorithm. (17th May 2019) - Ghosh, Pinaki; Mahesh, T.R.
Radio frequency identification (RFID) is now becomes a core technology in the internet of things (IoT). It has gained the attention of industry and academia in tremendous ways. Due to the openness in nature, RFID tags suffer with potential security threats. One of the major threats is privacy leakage during the authentication process. A strong privacy preserving authentication (PPA) protocol is always a need to this system. In this paper we have proposed salted secure hash-based mutual authentication protocol as a solution. The proposed protocol is designed to sends random response from tag to the server without disclosing its identity information to intermediate entities like readers. It also updates secret keys without transmitting the secret values.